LUMA™™ Cervical Imaging System. (March 2007) - Kendrick, James E; Huh, Warner K; Alvarez, Ronald D
For approximately 30 years colposcopically directed biopsy of the uterine cervix has been the gold standard for the detection of cervical intraepithelial neoplasia (CIN) and cancer following an abnormal Papanikolaou (Pap) smear. Recent technological advancements utilizing properties of fluorescence, reflectance and spectroscopy intrinsic to in vivo tissues, have led to the development of a useful adjunct to improve colposcopic detection of high-grade CIN. The addition of the LUMA™™ (MediSpectra, Inc., MA, USA) cervical imaging system to colposcopy has been shown in two prospective, randomized controlled trials to result in a 25% or greater increase in the true positive biopsy rate of colposcopy for patients with atypical squamous cell or low-grade squamous intraepithelial lesions on Pap smear, with only a 4% increase in the false-positive rate, versus that of colposcopy alone. The US FDA approved this device in March 2006 to be used to enhance the sensitivity of colposcopic examinations of women with abnormal cervical cytology, in an effort to further reduce the incidence of cervical cancer.